BRIDGING THE SERVICE GAP FOR OLDER ADULTS WITH MENTAL HEALTH NEEDS - White, D.L. (Innov Aging, 2017)
Although emotional well-being generally increases with age, many older adults are at risk for poor mental health. Declining physical health and increased social isolation place many at risk for depression and anxiety. Also, people who have been diagnosed with a serious mental illness (e.g., schizophrenia, bipolar disorder) are living longer, and they experience age-related changes prematurely. Brain injuries such as those related to falls and other trauma are on the rise. Dementia, the sixth leading cause of death, is increasingly recognized as a major public health concern. Multiple co-morbidities that often accompany these conditions further compromise well-being. U.S. health and social service systems have not prioritized the needs of older adults with these multiple and complex needs. Services are fragmented as agencies work in silos with different funding priorities, eligibility requirements and knowledge bases. As a result, we see high rates of health care utilization, poor quality of life, and increased mortality. The State of Oregon has launched several initiatives designed to build bridges between service systems and ultimately fill gaps in services to older adults. This symposium will report on results from three of these initiatives: 1) coordinating services across systems through a new workforce, “Older Adult Behavioral Health Specialists;” 2) implementing evidence-based programs for older adults with moderate depression using strength-based, problem solving approaches (e.g., PEARLS, Healing Pathways); and 3) a dementia training program that includes a focus on people with both serious mental illness and dementia, emphasizing person-centered thinking and planning.